A variant in GRN of Spanish origin presenting with heterogeneous phenotypes - M. Menéndez-González; A. García-Martínez; I. Fernández-Vega; A. Pitiot; V. Álvarez (Neurología (English Edition))
Introduction: The variant c.1414-1G>T in the GRN gene has previously been reported as probably pathogenic in subjects of Hispanic origin in the American continent. Methods: We report 5 families of Spanish origin carrying this variant, including the clinical, neuroimaging, and laboratory findings. Results: Phenotypes were strikingly different, including cases presenting with behavioral variant frontotemporal dementia, semantic variant primary progressive aphasia, rapidly progressive motor neuron disease (pathologically documented), and tremor-dominant parkinsonism. Retinal degeneration has been found in homozygous carriers only. Ex vivo splicing assays confirmed that the mutation c.1414-1G>T affects the splicing of the exon, causing a loss of 20 amino acids in exon 11. Conclusions: We conclude that variant c.1414-1G>T of the GRN gene is pathogenic, can lead to a variety of clinical presentations and to gene dosage effect, and probably has a Spanish founder effect. Resumen: Introducción: La variante c.1414-1G > T en el gen GRN ha sido reportada previamente como probablemente patogénica en sujetos del continente Americano de origen Hispano. Métodos: Reportamos cinco familias de origen Español portadoras de la mencionada variante. Se presentan las características clínicas, de neuroimagen y de laboratorio. Resultados: Los fenotipos encontrados difieren llamativamente entre los distintos casos, incluyendo presentación como demencia frontotemporal variante conductual, variante semántica de afasia progresiva primaria, enfermedad de neurona motora rápidamente progresiva (con confirmación neuropatológico) y parkinsonismo de predominio tremórico. Degeneración retiniana fue evidenciada únicamente en portadores homocigotos. Ensayos de splicing ex vivo confirman que la mutación c.1414-1G > T afecta el splicing del exón, causando una pérdida de 20 aminoácidos en el exón 11. Conclusiones: Concluimos que la variante c.1414-1G > T del gen GRN es patogénica, puede causar presentaciones clínicas diversas, efecto de dosis génica y probablemente represente un efecto fundador de origen Español.